Some fat in the fire - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Since 1 January 2002, the European Union has applied lower import tariffs on some oils and fats from developing countries, primarily for sunflower, groundnut, ricinus and palm oils. Bad news for ACP countries, who already enjoyed preferential...